P71 LEFT MAIN ANGIOPLASTY: TWENTY YEARS OF EXPERIENCE OF A HIGH–VOLUME SINGLE CENTRE WITH ANGIOGRAPHIC FOLLOW–UP. (18th May 2022) - Franzé, A; Quadri, G; Cerrato, E; Rolfo, C; Tomassini, F; Zanda, G; Piedimonte, G; Varbella, F
Abstract: Long term result of left main angioplasty nowadays is still debated. The retrospective analysis of our reporting software detected from 11/2000 to 11/2021 a total of 956 patients that underwent percutaneous transcatheter coronary angioplasty (PTCA) on unprotected left main with de–novo lesions. The average age of our sample was found to be 72 years old (+–10), mainly male (76, 4%). The prevalence of hypertension was 74, 6%, of diabetes was 26, 2%, of dyslipidaemia was 51, 7%, of smoke was 49, 8%. The indication for PTCA was ACS in 63, 8% of patients (610), in particular STEMI were the 19, 5% (186) of patients, NSTEMI were the 29, 4% (281) and unstable angina were the 15% (143). Of these ACS in 29 patient the presentation was with cardiac arrest. Patient with CCS were the 36, 2% (346). Intubation was necessary in 36 patients. Intra–aortic balloon pump was used in 341 patients (35, 7%), in 90, 9% of cases before the beginning of the procedure. Radial (45, 1%) and femoral access (54, 9%) were equally used. Among 773 bifurcations (the 80% of patients), a single stent technique was used in the 66, 5% of cases (provisional). Considering the two stent techniques, the Crush was used in 12, 7% of cases, the Culottes in 11, 1%, the TAP in 6, 7%, and the SKS in the 3%. Final kissing balloon was achieved in the 80, 2% of bifurcations. Intracoronary imaging was used in the 48, 4% of cases (463 patients), mainly IVUS (457). In our centre, as experimental protocol, an angiographic follow–up at 1 year is performed in most of patients that undergo angioplasty on left main. Overall, an angiographic follow–up is available for 607 patients (the 63, 5% of patients) with an average lenth of 546 days. The indication for the new angiography was STEMI in 1, 9% of patients, NSTEMI in 4, 1%, unstable angina in 2, 4%, stable angina in 8, 6%, and only protocol in the 46, 5%. Re–stenosis with redo of angioplasty on left main happened in 89 patients (14, 7%), but of these only in 50 patients (56%) was clinically driven. Stent thrombosis was in all cases very–late (average 1609 days) and happened only in 7 patients (1, 2%). A new PTCA in non–left main segments was performed in 153 cases (25, 2%) and was clinically driven only in 50, 4% of patients. Angiographic follow–up of complex PTCA such as those on unprotected left main could, in addition to potentially preventing adverse events, also provide interesting and real–world data about the effectiveness of the procedures and of their various technical aspects.